High-resolution imaging of a coal seam based on quasi-2D TEM inversion - Su, Chao; Ma, Guoqing; Liu, Cai; Liu, Yunhe; Zhang, Bo (Frontiers in Earth Science, 2023)
In a sedimentary environment, the conventional one-dimensional (1D) inversion based on the horizontal layered model has difficulty restoring the resistivity distribution of the inclined strata when a coal seam has some dip angle or a small interval between layers. In such cases, the inversion resistivity exhibits horizontal discontinuities, which cannot accurately represent actual geological conditions. Therefore, in view of the good horizontal continuity of the underground electrical structure of sedimentary strata, we propose a high-resolution inversion method based on weighted horizontal and vertical constraints. As a quasi-two-dimensional (2D) inversion, this not only ensures the horizontal continuity of resistivity and recovers the inclined strata, but also improves the vertical resolution. Because the constrained factor has a significant influence on the inversion result, different constrained factors are applied in the horizontal and vertical directions to adjust the constraint strength on the model parameters of each layer and the continuity of the layer interface. In the numerical experiments, we design synthetic models with different tilt angles and layer spacings to test the inversion method and optimize the constrained factors used for coal seam detection. Finally, the transient electromagnetic (TEM) field data processing results in Inner Mongolia show that the resistivity distributions of sedimentary strata can be accurately restored by the new method, and the inversion results are consistent with known geological information.